2010
DOI: 10.1007/s00213-010-2047-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the discriminative stimuli produced by either the neuroactive steroid pregnanolone or the benzodiazepine midazolam in rats

Abstract: Rationale-Neuroactive steroids might be therapeutic alternatives for benzodiazepines because they have similar anxiolytic, sedative and anticonvulsant effects, and their actions at different modulatory sites on GABA A receptors might confer differences in adverse effects.Objectives-This study used drug discrimination to compare discriminative stimuli produced by positive GABA A modulators that vary in their site of action on GABA A receptors.Methods-Two groups of rats discriminated either 3.2 mg/kg of pregnano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…Both kinds of studies were used previously to demonstrate similarities in the role of GABA A receptors in the discriminative stimulus effects of pregnanolone and midazolam. In substitution studies, positive GABA A modulators produced drug-lever responding and drugs with actions at other receptors produced vehicle-lever responding in rats discriminating either pregnanolone from vehicle or midazolam from vehicle (Bai and Gerak 2011), demonstrating the importance of GABA A receptors in the discriminative stimulus effects of pregnanolone and midazolam. Drug combination studies further support the role of GABA A receptors in these effects.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Both kinds of studies were used previously to demonstrate similarities in the role of GABA A receptors in the discriminative stimulus effects of pregnanolone and midazolam. In substitution studies, positive GABA A modulators produced drug-lever responding and drugs with actions at other receptors produced vehicle-lever responding in rats discriminating either pregnanolone from vehicle or midazolam from vehicle (Bai and Gerak 2011), demonstrating the importance of GABA A receptors in the discriminative stimulus effects of pregnanolone and midazolam. Drug combination studies further support the role of GABA A receptors in these effects.…”
Section: Discussionmentioning
confidence: 99%
“…These training doses were selected because previous studies indicated that the potency of pregnanolone and midazolam to produce drug-lever responding would be similar across the two groups with these training doses (Bai and Gerak 2011). Sessions were divided into 15-min cycles and there could be up to 8 cycles in a session.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations